IMPLEMENTASI PENGEMBANGAN EMPATI LINTAS BUDAYA DALAM MEWUJUDKAN SEKOLAH RAMAH ANAK DI SEKOLAH MULTIKULTURAL - Pasulu, Yemima El-roi; Murniarti, Erni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Cross-cultural empathy is a culture that must be built within multicultural schools, not merely used as a slogan, but rather as a culture. However, the problem arises that schools remain conventional and struggle to implement Child-Friendly Schools, inadvertently depriving children of their rights. This study aims to analyze the implementation of cross-cultural empathy development in realizing inclusive, child-friendly schools. The research approach used was a qualitative case study design, which utilized the reflective experiences of teachers, students, and school administrators as sources of meaning. Data were collected through observation, in-depth interviews, and documentation studies. The results indicate that cross-cultural empathy development is implemented through the integration of empathy values ​​into the learning process, dialogic relationships between teachers and children, and the formation of a school culture that upholds respect for differences within their world. Teachers act as facilitators, fostering ethical awareness and mutual understanding through participatory learning experiences that support the learning process. Child-friendly schools are realized when cross-cultural empathy becomes a lived value that creates a safe, humane school climate that respects children's rights.